Asset exposure of Asian cities to natural hazards - Metro Manila - Wong, John Ming Ba (2015)
Natural disasters occur throughout the world. The timing of natural disasters can be nearly impossible to predict. It is however, possible to predict the assets exposed to natural disasters. Knowing how much assets are exposed will play a significant role in disaster management, enabling countries to be prepared to handle the losses occurred during a natural disaster. This project focuses on Metro Manila, the National Capital Region of the Philippines. The Philippines has been plagued by many natural disasters, and is well known for frequent typhoons and flooding. It is therefore an ideal location to carry out the research, as the results obtained could possibly be put to good use. Building construction value is used as an indicator of the assets exposed to natural hazards in Metro Manila. The population ratio of Metro Manila vs Philippines was used to derive relevant values which were only available for Philippines itself to scale down to Metro Manila. A power law scaling equation was then used to forecast the future building construction values of Metro Manila. This was done using population predictions from the United Nations and the building construction values were predicted to the year 2100. An alternative method of forecasting the future building construction values using GDP as a scaling factor is also included.